Dakwah Islamiyah Di Era Milenial - Abdul Hamid Bashori; Moh. Jalaluddin (Sekolah Tinggi Agama Islam Publisistik Thawalib Jakarta, 2021)
The purpose of writing is to explain the implementation of Islamic da'wah in the millennial era. The writing method is descriptive qualitative type with a literature study approach. The results of the writing show that Islamic da'wah needs to be carried out by following the developments of the times and technology in this millennial era with the aim that da'wah actors are more up to date in utilizing millennial da'wah media to provide knowledge, understanding, and understanding of Islam to da'wah targets.